THE INFLUENCE OF CORPORATE GOVERNANCE ON THE PERFORMANCE OF MANUFACTURING COMPANIES WITH EVA APPROACH - Dianita, Rina (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to examines the influence of good corporate governance on the performance of manufacturing companies with EVA approach. Corporate governance components in this study is the size of independent board of commissioners, institutional ownership, managerial ownership and the size of the audit committee. The company's performance is measured by EVA. Population in this study is the manufacturing company basic industry and chemical sectors listed on the Indonesia Stock Exchange in 2012 and 2013, the sampling method used is purposive sampling method obtained a sample amounts to 40 manufacturing company basic industry and chemical sector in the period 2012-2013. Data collection techniques used in this study is documentation and pooling with multiple regression analysis method that uses data of annual financial reports listed on the Indonesian Stock Exchange. These results of the study indicates that good corporate governance have a significant effect to company’s performance (EVA) with managerial ownership variables and size of the audit committee. The higher managerial ownership and the audit committee, it will improve the company's performance through improved quality of earnings and corporate value. Variable size of independent Board of Commissioners and institutional ownership has no significant effect on company’s performance (EVA).    Keywords: good corporate governance, size of the independent board of commissioners, institutional ownership, managerial ownership, audit committee, company's performance (EVA)